If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 2x + 5 = 4x + -3 Reorder the terms: 1 + 5 + 2x = 4x + -3 Combine like terms: 1 + 5 = 6 6 + 2x = 4x + -3 Reorder the terms: 6 + 2x = -3 + 4x Solving 6 + 2x = -3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 2x + -4x = -3 + 4x + -4x Combine like terms: 2x + -4x = -2x 6 + -2x = -3 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + -2x = -3 + 0 6 + -2x = -3 Add '-6' to each side of the equation. 6 + -6 + -2x = -3 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = -3 + -6 -2x = -3 + -6 Combine like terms: -3 + -6 = -9 -2x = -9 Divide each side by '-2'. x = 4.5 Simplifying x = 4.5
| .4(x+2)-7(x+2)=-.3x-.6 | | 3m+6=6+3m | | x-.6x+1.2=-.88(x-.43) | | 5x-4=7x+20 | | 15=3/7x | | 40=a+5 | | 5r-(2n+8)=16 | | -2x+4+3x=4 | | 6+2(3j+2)=4(1+j) | | 7p-12=-2 | | -10x+58+6x+41=111 | | 6-9x=5x-9x-29 | | [7x-10]=73 | | 5x-14=-2x+15 | | -6+8p=-16+4p | | x=-5y-7 | | 2-(-x)=-4 | | -5=-5(2n-3) | | 4a^3-25a=0 | | -29=7x-5-x | | -4(x-5)=-7+28 | | 3y-3=13y+77 | | 6w^2+16w+8=0 | | 21x-8=5(4x+2)-2 | | 9=24-3p | | 12+n-2+6n=n-2+8n | | 10x+1=2(3x+9)-1 | | 25x(x+5)+10y=6.50 | | 2x+7-3x=x+21 | | 3x+1+5x-3=90 | | 6y-9y=21 | | w=56+(22+3) |